Synthesis of Uronic Acid 1‐Azasugars as Putative Inhibitors of α‐Iduronidase, β‐Glucuronidase and Heparanase. (3rd January 2023) - Doherty, Gareth G.; Ler, Geraldine Jia Ming; Wimmer, Norbert; Bernhardt, Paul V.; Ashmus, Roger A.; Vocadlo, David J.; Armstrong, Zachary; Davies, Gideon J.; Maccarana, Marco; Li, Jin‐ping; Kayal, Yasmin; Ferro, Vito
Abstract: 1‐Azasugar analogues of l ‐iduronic acid (l ‐IdoA) and d ‐glucuronic acid (d ‐GlcA) and their corresponding enantiomers have been synthesized as potential pharmacological chaperones for mucopolysaccharidosis I (MPS I), a lysosomal storage disease caused by mutations in the gene encoding α‐iduronidase (IDUA). The compounds were efficiently synthesized in nine or ten steps from d ‐ or l ‐arabinose, and the structures were confirmed by X‐ray crystallographic analysis of key intermediates. All compounds were inactive against IDUA, although l ‐IdoA‐configured 8 moderately inhibited β‐glucuronidase (β‐GLU). The d ‐GlcA‐configured 9 was a potent inhibitor of β‐GLU and a moderate inhibitor of the endo‐β‐glucuronidase heparanase. Co‐crystallization of 9 with heparanase revealed that the endocyclic nitrogen of 9 forms close interactions with both the catalytic acid and catalytic nucleophile. Abstract : Potential chaperones : Uronic acid 1‐azasugars (1‐ N ‐iminosugars) with l ‐IdoA and d ‐GlcA configurations and their corresponding enantiomers were efficiently synthesized from d ‐ or l ‐arabinose. Compounds were evaluated for the inhibtion of α‐iduronidase, β‐glucuronidase and heparanase, and for activity as potential pharmacological chaperones for mucopolysaccharidosis I (MPS I).